Модели реализации комплексной стратегии управления отходами - Скарга-Бандурова, И. С. (НТУ "ХПИ", 2013)
Предложена новая модель для автоматизации решения задач управления потоком отходов, основанная на методах интервально-параметрического линейного программирования (ИЛП), которая учитывает основные операции обращения с отходами. Общий подход может быть применен к широкому спектру природоохранных задач

The model for automation of the waste flow control was proposed. It grounded on the methods of interval-parameter linear programming and was developed according to the requirements of the legislation of Ukraine. The general approach is applicable to a wide range of environmental problems
A model for implementation of integrated solid waste management strategy
Keywords: автоматизация; управление потоком отходов; метод; интервально-параметрическое линейное программирование; природоохранная задача; обработка; температура; захоронение; model; automation; flow control of waste; method of interval-parametric linear programming; environmental problems